Therapy-induced senescence in breast cancer: an overview - Suraj Narayanan Chembukavu; Andrew J Lindsay (Open Exploration Publishing Inc., 2024)
Outcomes for women with breast cancer have improved dramatically in recent decades. However, many patients present with intrinsic drug resistance and others are initially sensitive to anti-cancer drugs but acquire resistance during the course of their treatment, leading to recurrence and/or metastasis. Drug therapy-induced senescence (TIS) is a form of drug resistance characterised by the induction of cell cycle arrest and the emergence of a senescence-associated secretory phenotype (SASP) that can develop in response to chemo- and targeted- therapies. A wide range of anticancer interventions can lead to cell cycle arrest and SASP induction, by inducing genotoxic stress, hyperactivation of signalling pathways or oxidative stress. TIS can be anti-tumorigenic in the short-term, but pro-tumorigenic in the long-term by creating a pro-inflammatory and immunosuppressive microenvironment. Moreover, the SASP can promote angiogenesis and epithelial-mesenchymal transition in neighbouring cells. In this review, we will describe the characteristics of TIS in breast cancer and detail the changes in phenotype that accompany its induction. We also discuss strategies for targeting senescent cancer cells in order to prevent or delay tumour recurrence.